The Effect Of Epsom Salt and Lemongrass Foot Soaks On The Alteration Of Blood Pressure In Hypertensive Pregnant Mothers In The Public Health Center Of Cigalontang 2021: - - Alvin Alvani Tresna A; Nunung Mulyani; Bayu Irianti (Media Informasi, 2023)
Hypertension is a condition where the systolic blood pressure is more than 120 mmHg, the diastolic blood pressure is higher than 80 mmHg. One of the health problems that has frequently appeared throughout pregnancy and can develop a health complication is hypertension in pregnancy. Based on Strait’s research (2012), hypertension in pregnancy is a prime factor in causing the deaths of mothers and their fetuses. Hypertension can be treated by pharmacology and non-pharmacology therapy. One of the non-pharmacology therapies is Epsom salt and lemongrass foot soak. The objective of this research is to know The Effect of Epom Salt and Lemongrass Foot Soak on the Alteration of Blood Pressure in Hypertensive Pregnant Women Year 2021. Method: The method used for this research is the quantitative method, using a pre-experimental design one group pretest-postest design. The observation has done twice, which is before and after the experiment. The sampling technique in this research is purposive sampling. The amount of the samples are 24 respondents. The statistic test is using the Wilcoxon test. Result: The results from the Wilcoxon statistic test obtained p Value 0,000 in means there is a change difference before and after the Epom Salt and Lemongrass foot soak in hypertensive pregnant women. Conclusion: There is an effect of Epsom salt and lemongrass foot soak on the alteration of blood pressure in hypertensive pregnant women.